Integrasi Pendidikan Lingkungan Hidup Melalui Masyarakat Pedesaan Sebagai Alternatif Menciptakan Kawasan Hijau Dengan Memanfatakann Sampah Botol Plastik Sebagai Media Tanam Toga Dengan Sistem Vertikultur - Dina Meris Maya Sari; Yudy Prasetyo; Agung Kurniawan (Penerbit STKIP PGRI Bangkalan, 2018)
The purpose of this paper is the utilization of plastic waste as a means of cultivation oftoga with vertikultur system through environmental education in the community.Implementation method using stages that there is action research class. The results ofresearch, In the first cycle of the process of securing a toga made by the community inaccordance with the target. Strategic location supports the community to plant togawith vertikultur system. However, the community is still less maximal in the process ofperga's daily toga. In the second cycle, the gowns are varied, the containers used indifferent colors, and the location is widespread. Treatment of toga has increased peopleare starting to care about the toga that has been planted. In addition, the toga is alsoused by the community for everyday purposes